Analytical techniques for X-ray polarization studies of rapidly rotating neutron stars and black holes - Loktev, Vladislav (fi=Turun yliopisto|en=University of Turku|, 2025)
Compact stellar remnants such as neutron stars and black holes attract not only mate¬rial from their surroundings but also the close attention of astronomers. The latter is because these objects constitute unattainable cosmic laboratories that showcase ex¬treme physics on a grand scale. The environments around these objects feature high, near-critical magnetic felds, gravitational warping of spacetime, and highly relativis¬tic motion of matter. In close binary systems, a compact object strips matter from a companion star, forming an accretion disk around itself. Infuenced by the intense gravity, matter falling onto a compact object will heat up to very high temperatures and emit X-rays. X-ray polarimetry emerges as a powerful tool for probing these exceptional sys¬tems. Polarization of light is inherently geometric in nature and often carries in¬formation about the physical properties of the system that is not accessible through just the intensity of the radiation. Hence, polarization measurements can reveal the structure of magnetic felds, the orientation of accretion disks, and the properties of coronae around them. My work was signifcantly shaped by the launch of the frst X¬ray polarimeter in the 21st century, the Imaging X-ray Polarimetry Explorer (IXPE) mission. I studied the ways in which we can extract information about the geometry and physical processes in X-ray binary systems from the spectral and polarimetric properties of these X-rays. Two subclasses of X-ray binaries underwent my scrutiny: accreting millisecond pulsars and black hole X-ray binaries. Accreting millisecond pulsars are neutron stars that accrete matter from a com¬panion star. Over the course of the evolution of the system, the neutron star is spun up to periods of a few milliseconds, and this rotation is so steady that it renders the systems into the most precise clocks in the universe. X-ray radiation emerges near the magnetic poles of the neutron star, and if the magnetic and rotation axes are mis¬aligned, as often happens, the radiation will be pulsed. A longstanding question for neutron stars is the equation of state of the matter in their cores, which connects the mass and radius of the star. Precise measurements and analysis of X-ray pulse pro¬fles can infer the geometrical properties of the system, which in turn can be used to constrain the equation of state of a neutron star. One particular challenge I focused on in my work is posed by the relativistic velocities of the surface of the neutron star, which deforms the neutron star into an oblate shape, affecting the observed pulse profles. The black hole X-ray binaries, on the other hand, pose different questions. The event horizon instead of a solid surface makes it notoriously diffcult to infer the spin rate of the black hole. The spin parameter must be inferred from the geometrical properties of the disk of accreting matter that forms around it. In the so-called soft state, the disk is geometrically thin and extends down to the innermost stable circular orbit, which is uniquely characterized by the spin of the black hole. However, con¬straining the geometry from X-ray spectral properties is not a straightforward task, especially so due to the radiation is twisted by the strong gravity of the black hole. My interest in these systems was to study the ways to connect the spectropolarimet¬ric properties of the X-ray radiation to the geometry of the system in a more quick and fexible way than traditional ray tracing techniques would allow.